1965
DOI: 10.3133/pp493
|View full text |Cite
|
Sign up to set email alerts
|

Trilobites of the Late Cambrian Pterocephaliid biomere in the Great Basin, United States

Abstract: The Pterocephaliid biomere is a biostratigraphic unit of stage magnitude that includes the most consistently fossiliferous parts of the Upper Cambrian in the Great Basin of western conterminous United States. The thickness of strata containing faunas of this biomere generally exceeds 500 feet. This interval includes units consisting of fine-grained detrital material and of clean carbonate rocks; the carbonate rocks probably represent sediments that composed a broad carbonate bank, and the units of detrital mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
210
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(220 citation statements)
references
References 3 publications
7
210
3
Order By: Relevance
“…Non-evolutionary changes in trilobite complexes, such as migrations, have been suggested, however, to be common especially at the beginning of the G. reticulatus Biozone (Rozanov et al 1992). Palmer (1965Palmer ( , 1979 also noted that diachronous boundaries of biostratigraphic units occurred in the Middle and Upper Cambrian, but he later suggested that the difference was not significant for biostratigraphic correlation (Palmer, 1984).…”
Section: The Middle-upper Cambrian Boundary In the Kulyumbe Sectionmentioning
confidence: 99%
“…Non-evolutionary changes in trilobite complexes, such as migrations, have been suggested, however, to be common especially at the beginning of the G. reticulatus Biozone (Rozanov et al 1992). Palmer (1965Palmer ( , 1979 also noted that diachronous boundaries of biostratigraphic units occurred in the Middle and Upper Cambrian, but he later suggested that the difference was not significant for biostratigraphic correlation (Palmer, 1984).…”
Section: The Middle-upper Cambrian Boundary In the Kulyumbe Sectionmentioning
confidence: 99%
“…It has mainly been recorded from North America (Walcott 1924;Kobayashi 1938;Palmer 1954Palmer , 1960Palmer , 1965a; other occurrences include the Gorny Altai Mountains (Romanenko and Romanenko 1967) and northern China (Zhu et al 1979).…”
Section: Remarksmentioning
confidence: 99%
“…Another trilobite from the Agnostus pisiformis Zone, Olenus alpha Henningsmoen, 1957 of Norway was considered a representative of Simulolenus Palmer, 19654 (Henningsmoen 1957aNikolaisen and Henningsmoen 1985), a genus characteristic of the Steptoean Dunderbergia Zone of the Great Basin, USA (Palmer 1965a). The specimens at hand differ from Simulolenus alpha (Henningsmoen, 1957) in having much larger dimensions, eye-ridges that are more backwardly oblique, and a sagittally much wider anterior border.…”
Section: Systematic Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations